(untitled) (Journal of the College of Basic Education, 2022)
Based current have marked (the role of the plastic elements in the read film image , and production meaning) on the premise that can read film picture , as well as watch them Because, film image phenomenon does not refer to themselves sometimes, but always refers to gloss meaning. So that it organized in the mechanism assumes the existence: A: visual stimuli material concrete signs constitute attend. B: sensory stimuli, intellectual and abstract are the signs of being the absence of evocation. The research problem represented in question on the nature of this mechanism and methods of regularity .The research go to goals, which was how to read the film image, and detection of plastic components in the read film image search, research has been enrolled in three sections came under the following headings: Section I: Introduction to understanding film image, The second topic: the mechanism of expression in the film image. And the third section : read meaning across the film image. The third chapter under the action title search and analysis of the sample and it was extracted search tool of indicators that have been out of the theoretical framework and according to the provisions of ideas and thoughts .and most prominent results that have been reached: 1-The visual highlight configurations in order to produce a specific meaning employ Fine symbols to support this mission. 2-film image able to produce meaning and consumption are singularly without the need for dialogue. 3-The camera movement has emerged to make the film image, say what you want, which underlines the unique property of the film image, its proximity to the movement. Among the most prominent conclusions have been reached was: 1- read film image, is the perception process first and then dropping thoughts second. 2-produced image elements on both end, part of the meaning and all together are producing the whole meaning. 3-There are permanent deliberate in the film image, so the plastic elements which are always in (the presence of a relationship) and meaning in (the absence of a relationship) always conjure and summon her. . Then search concluded with a list of sources